PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DEBT TO EQUITY PADA PERUSAHAAN PERBANKAN TAHUN 2010-2016 - Zulkifli Umar; Cut Fitrika Syawalina; M. Yunus Usman; Khairun Nufus (KOLEGIAL, 2018)
This research was conducted on banking companies listed on the Indonesia Stock Exchange in 2014-2016. With the aim of testing and knowing the effect of profitability, company size, debt to equity on the timeliness of financial statement submission. The population in this study were 42 banking companies for each period, the amount of data in this study was 126 financial statements. The data used in this study is secondary data with the analysis technique using multiple linear regression and binary linear regression (logistic). The results show that partial profitability does not affect the timeliness of financial statement submission, and company size partially influences the timeliness of financial statement submission, while debt to equity partially does not affect the timeliness of financial statement submission. The three independent variables simultaneously influence the timeliness of the submission of financial statements, with the magnitude of the influence of 9% while the remainder is influenced by other variables not included in this study